Using Cholinesterases and Immobilized Luminescent Photobacteria for the Express-Analysis of Mycotoxins and Estimating the Efficiency of Their Enzymatic Hydrolysis - Elena Efremenko; Olga Maslova; Nikolay Stepanov; Anvar Ismailov (Toxins, 2021)
Novel sensitive analytical agents that can be used for simple, affordable, and rapid analysis of mycotoxins are urgently needed in scientific practice, especially for the screening of perspective bio-destructors of the toxic contaminants. We compared the characteristics of a rapid quantitative analysis of different mycotoxins (deoxynivalenol, ochratoxin A, patulin, sterigmatocystin, and zearalenone) using acetyl-, butyrylcholinesterases and photobacterial strains of luminescent cells in the current study. The best bioindicators in terms of sensitivity and working range (μg/mL) were determined as follows: Photobacterium sp. 17 cells for analysis of deoxynivalenol (0.8–89) and patulin (0.2–32); Photobacterium sp. 9.2 cells for analysis of ochratoxin A (0.4–72) and zearalenone (0.2–32); acetylcholinesterase for analysis of sterigmatocystin (0.12–219). The cells were found to be more sensitive than enzymes. The assayed strains of photobacterial cells ensured 44%–83% lower limit of detection for deoxynivalenol and sterigmatocystin as compared to the previously known data for immobilized luminescent cells, and the range of working concentrations was extended by a factor of 1.5–3.5. Calibration curves for the quantitative determination of patulin using immobilized photobacteria were presented in this work for the first time. This calibration was applied to estimate the enzyme efficiency for hydrolyzing mycotoxins using zearalenone and His6-tagged organophosphorus hydrolase as examples.